Microbiological analysis of acute infections of the nail fold on the basis of bait thread test - Tomczak, Hanna; Dańczak-Pazdrowska, Aleksandra; Polańska, Adriana; Osmola-Mańkowska, Agnieszka; Pazdrowski, Jakub; Błażejewska-Gąsior, Wioleta; Horla, Anna; Hasse-Cieślińska, Marta; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : An acute infection of the nail fold, called paronychia, is a common clinical problem. The basis for the implementation of the treatment is the result of microbiological examination. Due to the rapid and painful course of infection, usually an empirical antimicrobial treatment prior to obtaining microbiological test results is introduced. Aim: The microbial analysis of acute infections of the nail fold. Material and methods: The study included 32 tests conducted on 31 patients of the Department of Dermatology. Microbiological analysis was performed with the use of the so-called bait thread test. Results : In 73% of analyzed cases microbiological examination revealed mixed microbiological flora. Most cultured microorganisms were: Enterococcus faecalis (14%), Staphylococcus aureus (12%), Candida albicans (9%), Enterobacter cloacae (8%), and Klebsiella pneumoniae (7%). Most cultured bacteria belonged to the families or genera of Enterobacteriaceae (36%), other cultured bacteria were staphylococci (26%), enterococci (16%), Candida species (14%), and Gram-negative non-fermenting bacilli (8%). Conclusions : The acute infection of the nail fold in the vast majority of cases is caused by mixed bacterial flora. A profile of isolated microorganisms suggests that the cause of the infection can be associated with neglect of hygiene. Fluoroquinolone and fusidic acid are recommended as the empirical therapy. Microbiological examination is the basis for the appropriate final treatment.